1987
DOI: 10.1103/physrevd.36.2813
|View full text |Cite
|
Sign up to set email alerts
|

Hadron spectrum on an183×42 lattice

Abstract: We present results for the hadron spectrum of quenched lattice QCD on an 1 g 3 X 4 2 lattice at /3=6.2. We compare r =f Wilson fermions with quark masses in the range m , / m , = 1 to 5 to staggered fermions with m , / m , = f to 2. In the overlap region we find that the spectra agree, and that both yield a 1 = 2 . 5 GeV, if we use m , to set the scale. We also find that the flavor symmetry of the staggered fermions is restored to a greater degree than at lower 8. However, for both types of fermion, the nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 24 publications
3
55
0
Order By: Relevance
“…To this aim we have made simulations of the S (t) ZM correlator both at periodic and zero-field boundary conditions and have studied behaviour of effective masses found from this correlator. In all cases we have found that effective S U(2) gluon mass turns out to be nonzero (thus confirming qualitative results of [4][5][6][7] on this issue) and have got the following estimate of M g in case of S U(2) group:…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…To this aim we have made simulations of the S (t) ZM correlator both at periodic and zero-field boundary conditions and have studied behaviour of effective masses found from this correlator. In all cases we have found that effective S U(2) gluon mass turns out to be nonzero (thus confirming qualitative results of [4][5][6][7] on this issue) and have got the following estimate of M g in case of S U(2) group:…”
Section: Discussionsupporting
confidence: 67%
“…The varying correlator S (t) obtained for β = 2.6 is plotted in figure 1. It worth noting that correlators S (t) found for ZF BCs at various lattice volumes are presented in the logarithmic scale by nearly straight lines which correspond to gluon "effective" masses independent of N t contrary to what was found for periodic boundary conditions (PBCs) in [4][5][6][7] (see also below).…”
Section: Periodic Vs Zero-field Bcs; Zm Correlatorsmentioning
confidence: 54%
“…In this region, the perturbative running coupling s ð 2 Þ diverges, and the confinement effect is extremely large, so that quark-gluon degrees of freedom are hidden and the system is described by hadrons. So far, the gluon propagator has been studied mainly in the Landau gauge both in analytic framework [14,15,[17][18][19] and in lattice QCD [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. In the UV region, the gluon propagator takes a massless perturbative form, 1=p 2 , apart from the tensor factor.…”
Section: Introductionmentioning
confidence: 99%
“…It should be emphasized that the gluon "mass" is not a directly measurable quantity, but it can be related to other physical quantities. The lattice results [123,124,125,126,127,10] seem to support this concept. Parisi and Petronzio [122] were first to introduce it into description of J/ψ decays.…”
Section: Cornwall's Approachmentioning
confidence: 66%
“…(112), (124) for this purpose.) The Unitary Equations (112), (123) have been solved by the method of iterations. The residuum (125), physical mass (126) and the mass function (124) have been evaluated at each step of the iteration procedure and substituted in the Unitary Equations until convergence is achieved.…”
mentioning
confidence: 99%